2018
DOI: 10.1111/cpr.12489
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA FAL1 functions as a ceRNA to antagonize the effect of miR‐637 on the down‐regulation of AKT1 in Hirschsprung's disease

Abstract: These results illuminated that FAL1 may work as a ceRNA to modulate AKT1 expression via competitively binding to miR-637 in HSCR, suggesting that it may be clinically valuable as a biomarker of HSCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 33 publications
(67 reference statements)
0
39
0
Order By: Relevance
“…CDK6, STAT3, AKT1) ( Table 2). In addition, miR-637 could be itself regulated by non-coding endogenous competitors other than solely circHIPK3, as described in other diseases (26)(27)(28)(29)(30)(31)(32)(33)(34) (Table 2).…”
Section: A Comprehensive Analysis Of Circ-0000284 (Circhipk3) In Ccamentioning
confidence: 93%
“…CDK6, STAT3, AKT1) ( Table 2). In addition, miR-637 could be itself regulated by non-coding endogenous competitors other than solely circHIPK3, as described in other diseases (26)(27)(28)(29)(30)(31)(32)(33)(34) (Table 2).…”
Section: A Comprehensive Analysis Of Circ-0000284 (Circhipk3) In Ccamentioning
confidence: 93%
“…To reveal how lncRNAs mediate transcription in colon adenocarcinoma through their influence on mRNA and miRNA binding, a ceRNA network based on the list of DElncRNAs, DEmiRNAs, and DEmRNAs were constructed and visualized using Cytoscape software. As shown in Figure S2, the lncRNA-miRNA-mRNA network was comprised of 135 lncRNA, 28 miRNA and 52 mRNA nodes (Table S4- 5). The majority of DEmRNAs were tumor-related genes including SERPINE1, NPTX1, HILPDA, PRSS22, PMAIP1.…”
Section: Construction Of the Cerna Networkmentioning
confidence: 99%
“…LncRNAs are ≥200 nucleotides in length and regulate an array of cell biological processes including chromatin remodeling, transcription, and post-transcriptional events. 4,5 The most recognized molecular mechanism of lncRNAs are to act as miRNA "sponges" to regulate downstream target genes. 6,7 LncRNAs act as competing endogenous RNAs (ceRNAs) to accelerate cancer proliferation, migration, and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…9 Up to now, many miRNAs such as miR- 150-5p, miR-143, miR-637, miR-483-3p, miR-1324, miR-215, miR-24-1, let-7a, miR-939, miR-770-5p, miR-369-3p, miR-483-5p, miR-206 and miR-214 have been shown to affect the occurrence and development of HSCR. [10][11][12][13][14][15][16][17][18][19][20][21] However, no research has explored the role of miR-100 to HSCR.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31] Recently, some researches indicated that miR-100 regulated the growth, differentiation and apoptosis of neurons and directly/indirectly affected HSCR-associated pathways. 8,10,12,16,[32][33][34] Considering that rs1834306 may be a potential function site of miR-100, we conducted a case-control study to explore the association between miR-100 rs1834306 A>G polymorphism and HSCR susceptibility in Southern Chinese population.…”
Section: Introductionmentioning
confidence: 99%